Evaluating Innovative Skills in the Campus Recruitment Program Using Mathematical Placement Techniques: A Case Study - Sumathi, P.; Jebaraj, J. (Prabandhan: Indian Journal of Management, 2012)
In this paper, a descriptive research study based on the placement training scenario is demonstrated. The author tried to identify the factors that would determine the successful utilization, satisfaction and implementation of mathematical innovative placement techniques by students. Through this study, educational institutions and placement policy makers in Indian and foreign companies would be more efficient in their attempt to explain, predict and account for factors that impede or facilitate the implementation of mathematical innovative placement techniques throughout the country’s placement environment. All the students have to develop, sharpen and deepen their understanding of innovative mathematical placement techniques, placement process and to enhance their problem - solving, reasoning and communication abilities while using innovative placement techniques in order to solve compelling problems in the placement procedure. For this to occur, rigorous training in mathematical placement techniques must be recognized, taught, and assessed in a problem-solving environment.